Comics as an Educational Tool to Increase Students’ Knowledge and Attitudes Toward Menarche - Nurhayati, Dian; Aprianti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Menarche is the first menstruation experienced by adolescent girls. Insufficient knowledge and attitudes related to menarche can lead to unpreparedness, resulting in feelings of shame, fear, confusion, and poor vulvar hygiene practices. Therefore, health education using comic media related to menarche is necessary. Objectives: This study aims to analyze the effectiveness of comic media in improving the knowledge and attitudes of elementary school students in facing menarche. Methods: This study employed a quasi-experimental design with a pre-test and post-test control group. The research sample consisted of 60 fifth-grade female students who had not yet experienced menarche, selected through total sampling and divided into two groups: 30 students in the control group and 30 in the intervention group. Data analysis was conducted using univariate and bivariate analyses, including paired t-tests and independent t-tests. Results: The results showed an increase in knowledge about menarche before and after the intervention in both the intervention and control groups, with a p-value <0.001 (p<α, α = 0.05), and an improvement in attitudes with a p-value <0.001 (p<α, α = 0.05). Significant differences were observed between the intervention and control groups in terms of knowledge (p-value <0.001, p<α, α = 0.05) and attitudes (p-value <0.001, p<α, α = 0.05). Conclusion: In conclusion, health education utilizing comic media about menarche is effective in enhancing the knowledge and attitudes of fifth-grade female students.